Monitoring children in the shopping mall using RFID technology-controlling module - Nurul Nadia, Yahya (2010)
Normally, security system at shopping mall still at the low level and unsecure. Nowadays, cases of losing children at'he shopping mall always happen due to old fashion of security system there. Monitoring Children In The Shopping Mall Using RFID Technology-Controlling Module is being developed as a high level of security system at the shopping mall to decrease this becoming worst problem in this country. Moreover, the risk of lost children in the shopping mall is really high. Usually parents bring along their children when go to shopping mall. Many parents cannot monitor their children at the hectic situation in the shopping mall. Normally, security guard can just monitor part of the shopping mall area. So the possibilities of the losing children to find are really low. This system is created to help the security guard in order to perform their task that is being responsible for the security purpose at the shopping mall. In the other hand it also can prevent the risk of lost children in the shopping mall. This system is all about Radio Frequency Identifier (RFID). RFID is the use of an object applied to or incorporated into a product, animal, or person for the purpose of identification and tracking using radio waves. Each child that entered the shopping mall must w94 the RFID band for the security purpose. This system will appear the alert message when the children are pass through the antennae that is located at the entrance. After that, the security guard will announce the parents name for them to take action.